Comparison of the effects of platinum and CeO2 on the properties of single grain, Sm–Ba–Cu–O bulk superconductors. (10th October 2016) - Zhao, Wen; Shi, Yunhua; Radušovská, Monika; Dennis, Anthony R; Durrell, John H; Diko, Pavel; Cardwell, David A
Abstract: SmBa2 Cu3 O7− δ (Sm-123) is a light-rare-earth barium-cuprate (LRE-BCO) high-temperature superconductor (HTS) with significant potential for high field industrial applications. We report the fabrication of large, single grain bulk [Sm–Ba–Cu–O (SmBCO)] superconductors containing 1 wt% CeO2 and 0.1 wt% Pt using a top-seeded melt growth process. The performance of the SmBCO bulk superconductors containing the different dopants was evaluated based on an analysis of their superconducting properties, including critical transition temperature, T c and critical current density, J c, and on sample microstructure. We find that both CeO2 and Pt dopants refine the size of Sm2 BaCuO5 (Sm-211) particles trapped in the Sm-123 superconducting phase matrix, which act as effective flux pinning centres, although the addition of CeO2 results in broadly improved superconducting performance of the fully processed bulk single grain. However, 1 wt% CeO2 is significantly cheaper than 0.1 wt% Pt, which has clear economic benefits for use in medium to large scale production processes for these technologically important materials. Finally, the use of CeO2 results generally in the formation of finer Sm-211 particles and to the generation of fewer macro-cracks and Sm-211 free regions in the sample microstructure.